52. Lower limbs motor evoked potentials intra-session reliability: A coil comparison study. Issue 12 (December 2017) - Gelibter, S.; Fichera, M.; Giordano, A.; Chieffo, R.; Comi, G.; Leocani, L.
Abstract : Our aim is to investigate intra-session reliability of lower limbs (LL) motor evoked potentials (MEPs) amplitudes elicited by Transcranial Magnetic Stimulation (TMS) and measured from Tibialis-Anterior (TA) and Abductor-Hallucis (AH), comparing double cone and circular coil. TMS was used in healthy subjects (HS) ( n  = 7) to elicit MEPs in TA and AH of both LL, at rest and during low level muscle contraction. Double cone and circular coil were used. Two sets of eight responses were recorded for each coil in a random order, using a stimulation intensity of 100% of the maximum stimulator output. Intra-session reliability was calculated using Intraclass correlation coefficients (ICC). Double cone and circular coil showed excellent intra-session reliability in TA and AH of both LL, at rest and during low level muscle contraction (ICC ⩾ 0.75 in all experimental conditions). Interestingly, circular coil failed to elicit measurable MEPs at rest in non-dominant limb in 3 out of 7 HS. Double cone coil is an efficient alternative to circular coil in order to measure LL MEPs amplitudes in HS. Since circular coil did not elicit MEPs in all HS, double cone coil could be more useful in neurological patients to better detect MEPs in cortico-spinal tract pathological conditions.